Advances in studies on the plant rhizosphere microorganisms in wetlands: A visualization analysis based on CiteSpace. (March 2023) - Wang, Yaqi; Bai, Junhong; Zhang, Ling; Liu, Haizhu; Wang, Wei; Liu, Zhe; Zhang, Guangliang
Abstract: Rhizosphere microorganisms and their interactions with plants in wetlands have recently attracted much attention due to their importance in enhancing plant environmental adaptation, removing wetland pollutants, and alleviating climate change. However, the fluctuating hydrological environment of wetlands leads to more complex dynamics in the rhizosphere environment. Research progress and hotspots concerning plant-rhizosphere microorganisms under special wetland environments are still kept unclear. To better understand the current research status, hotspots and trends of rhizosphere microorganisms in wetlands, we used CiteSpace bibliometric software to visualize and analyze 231 English-language publications from the Web of Science core collection database. Here, we reviewed the role played by various countries, institutions, and scholars in the studies of plant rhizosphere microorganisms in wetlands based on cooperation network analysis. We discussed the shift from bioremediation and nutrient removal to rhizosphere microbial community composition as a research hotspot for plant rhizosphere microorganisms in wetlands according to keyword co-occurrence and clustering analysis. Finally, we highlighted that more attention should be paid to the ecological functions of rhizosphere microorganisms in different wetland ecosystems, and the plant‒microbe microinterface processes and interaction patterns should be explored in depth to provide new indicators for the evaluation of wetland ecosystem functions. Graphical abstract: Image 1 Highlights: First application of bibliometrics to analyze plant rhizosphere microorganisms in wetlands. Countries, institutions and authors that play an important role in this field are identified. Research hotspots in this field are bioremediation and microbial community analysis. Research prospects of plant rhizosphere microorganisms in wetlands are summarized.